Prevalence Trichomoniasis and Candidiasis For Symptomatic Pregnant and Non Pregnant Women in Iraq - Dhilal Mahdi AL-Muathen; Hayat Ghaith Sachit (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2018)
The prevalence of Trichomonas vaginalis (TV) and Candida albicans (CA) has been determined in 182 symptomatic married women (70 pregnant and 112 non pregnant) randomly selected from private gynecology clinics in Baghdad city. The relationship between infection and some risk factors was assessed.